2004
DOI: 10.1159/000079695
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Resistance against Antibiotics in Bacteria Isolated from the Lower Urinary Tract of an Outpatient Population of Spinal Cord Injury Patients

Abstract: Objective: To investigate changes of the bacterial spectrum and susceptibility in bacteria isolated from urine samples of spinal cord injury patients followed in a strict outpatient setting. Subjects and Methods: Due to neurogenic dysfunction, urinary tract infections are common in spinal cord injury patients. Nosocomial urinary tract infections and resistance against antibiotics are increasing problems in hospitalized spinal cord injury patients. Urine samples were obtained by aseptic catheterization during 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 7 publications
2
25
0
2
Order By: Relevance
“…patients, not only hospital but also community-residing patients have problems associated with antibiotic-resistant bacterial colonization or infection due to catheter-associated voiding and frequent antibiotics usage. 5,6,14 However, compared with community-dwelling patients, isolates from hospital-dwelling SCI patients showed higher resistance rates to the majority of antimicrobial agents that were investigated. In related studies, trimethoprim-sulfamethoxazole, amoxicillinclavulanic acid and second or third generation of cephalosporins are generally recommended for the empirical treatment of UTI in patients with SCI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…patients, not only hospital but also community-residing patients have problems associated with antibiotic-resistant bacterial colonization or infection due to catheter-associated voiding and frequent antibiotics usage. 5,6,14 However, compared with community-dwelling patients, isolates from hospital-dwelling SCI patients showed higher resistance rates to the majority of antimicrobial agents that were investigated. In related studies, trimethoprim-sulfamethoxazole, amoxicillinclavulanic acid and second or third generation of cephalosporins are generally recommended for the empirical treatment of UTI in patients with SCI.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] The results of these studies may help to select proper antimicrobial agents during empirical therapy for UTI. However, these studies have only assessed the outpatient SCI population.…”
Section: Introductionsmentioning
confidence: 99%
“…The authors concluded that antibiotic treatment should be limited to symptomatic UTIs and be initiated after sensitivity testing only. 15 Until today, however, no data concerning a safe and effective alternative treatment are available. Thus, antibiotic prophylaxis seems to be the method of choice today.…”
Section: Abbreviation: Uti Urinary Tract Infectionmentioning
confidence: 99%
“…UTIs are considerably more frequent because of urinary catheter use, residual urine in the bladder due to incomplete emptying, renal stones, obstructed urinary outflow, dysregulation of the autonomic nervous system, and an unbalanced bladder evacuation. These are significant causes of morbidity and mortality (1,2). Although UTIs occur in 22% of patients with acute SCI in the first 50 days, the UTI prevalence is approximately 20% in patients with chronic SCI (3).…”
Section: Introductionmentioning
confidence: 99%